Clinical variables associated with no-reflow after percutaneous coronary intervention in ST-segment elevation myocardial infarction: Secondary analysis of the PERSTEMI I and II study - Paredes-Paucar, Cynthia (2022)
Objective. To determine the clinical factors associated to no-reflow after percutaneous coronary intervention (PCI) in patients with ST-segment elevation myocardial infarction (STEMI) in Peru. Materials and methods. Case - control retrospective study, derived from the PERSTEMI (Peruvian Registry of ST-elevation myocardial infarction) I and II study. Cases (group 1) were those patients who presented no-reflow after PCI, defined by a TIMI flow < 3, and controls (group 2) were those with a TIMI 3 flow after the intervention. Clinical and angiographic variables were compared between both groups, and a multivariate analysis was performed looking for associated factors to no-reflow. Results. We included 75 cases and 304 controls. The incidence of no-reflow was 19.8%. There was a higher frequency of no-reflow in patients with primary PCI compared to the pharmacoinvasive strategy, in patients with one-vessel disease and in those with TIMI 0 before PCI. In-hospital mortality and heart failure were higher in patients with no-reflow (21.3% vs. 2.9% and 45.3% vs. 16.5, respectively; p<0.001). After the multivariate analysis, the ischemia time > 12 hours, Killip Kimball (KK) > I, TIMI 0 before PCI, and one-vessel disease were the factors significantly associated with no-reflow after PCI. Conclusions. The ischemia time greater than 12 hours, the highest KK score, the presence of an occluded culprit artery (TIMI 0) before PCI and an one-vessel disease, were factors independently associated to no-reflow in patients with STEMI in Peru.